Modeling and forecasting of the hospital occupation rate by means of simultaneous equations: A management tool - Mariano Bayer, Fábio; Souza, Adriano Mendonça (Revista Gestão da Produção Operações e Sistemas, 2007)
Due to the well-known importance of the “Hospital Universitário de Santa Maria – HUSM” (University Hospital of Santa Maria) – a reference in the state of Rio Grande do Sul xx – when it comes to Public Health Care xx , and due to the lack of scientific methods, which enable xx better management, it is common sense to contribute with xx statistical forecasting models, used as an auxiliary tool in order to change the situation. In this study, HUSM real data were used and were monthly collected xx, from January 2000 to December 2005, searching for hospital occupation rate (HOR) in three hospital admission sectors, which are: General Hospital (GH), Emergency Room (ER) and Psychiatric Unit (PU). The methodology used is the model of Simultaneous Equations with Two-Stage Least Square estimator, in which the variables considered as endogenous are the (HOR) in the three sectors and the pre-determined ones are the Average Stay (AS), Renewing Rate (RR) and the Replacement Interval Rate (RIR). Taking forecasting into account, managers can get better organized in order to serve a larger number of patients, as well as to lower hospital costs, thus increasing the system efficiency. Keywords: Simultaneous Equation Models; Forecasting and Short-term planning; Public Health Care.